Determinants Factor of Technical Efficiency in Machinery Manufacturing Industry in Malaysia - Muhammad Syafiq Abdul Latif; Mohd Fahmy Abdullah; Lai Wei Sieng (International Journal of Supply Chain Management, 2019)
Machinery manufacturing industry has been introduced since the beginning of the industrial era from European countries and developed until today. However, major challenges in machinery industry still driven by traditional production factors such as capital and labour that caused the industry still left out. Thus, the objective of the study are to analyse the level of TE and identifying determinant factors influenced to technical efficiency in the machinery manufacturing industry in Malaysia. The study was conducted by using the method of Data Envelopment Analysis (DEA) two stages. The first stage involves the calculation a score of efficiency through the DEA by using firm’s data while the second stage Regression Tobit Analysis used to identify significant factors influencing to technical efficiency in machinery industrial. This firm’s data are categorized into 3 sub-industry 3-digit according to the Malaysian Standard Industrial Classifications which are consists of Manufacture Of General Purpose Machinery, Manufacture Of Special Purpose Machinery and Manufacture Of Installation Machinery Industrial And Equipment. A total of 636 machinery industry firms were involved in this study. Results showed the average efficiency score is at the medium level while the determinant factors were significant are wage rates, the standard of education and research and development (RD). The implications of this study shows that the machinery industry should focus their attention to the significant factors to improve the level of technical efficiency of the machinery industry.